Faktor-Faktor yang Mempengaruhi Terjadinya Gangguan Tidur pada Anak dengan Leukemia Limfoblastik Akut yang Menjalani Kemoterapi - Andrye Fernandes; Yessi Andriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine the relationship between these factors and sleep disorders and determine the factors that most influence the occurrence of sleep disorders in ALL children undergoing chemotherapy. The design of this research is descriptive-analytic with a cross-sectional approach. The results showed a statistically significant relationship between the type of ALL, chemotherapy regimen, hemoglobin levels, fatigue, pain, and anxiety with a value of (p<0.005). In conclusion, pain and anxiety factors are the most influencing sleep disorders. Cancer and treatment, physiological, and psychological factors are related to the occurrence of sleep disturbances that will affect the quality of life of the next child. Keywords: Sleep Disorders, Chemotherapy, Acute Lymphoblastic Leukemia